Respostas
respondido por:
4
{ ( 2*10^8 - 1)/3 - ( 2*10^10 - 1 )/3 } / { ( 10^10 - 10^8 )} =
{( 2 * 10^8 - 1 - 2 * 10^10 + 1 )/ 3} * { 1/ 10^10 - 10^8 } =
COLOCANDO 10* EM EVIDÊNCIA
{10^8 ( 2 - 2 * 10² )/3 } * { 1/ [ 10^8 ( 10² - 1 ) ] =
{( 2 - 200)/3 } * (1/99 ) = - 198/3 * 1/99 = - 66/99 = - 2/3 ****
{( 2 * 10^8 - 1 - 2 * 10^10 + 1 )/ 3} * { 1/ 10^10 - 10^8 } =
COLOCANDO 10* EM EVIDÊNCIA
{10^8 ( 2 - 2 * 10² )/3 } * { 1/ [ 10^8 ( 10² - 1 ) ] =
{( 2 - 200)/3 } * (1/99 ) = - 198/3 * 1/99 = - 66/99 = - 2/3 ****
dsilvahenrique:
Obrigado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás